Driving Behaviors 2–3 Years After Traumatic Brain Injury Rehabilitation: A Multicenter Case-Control Study - McKerral, Michelle; Moreno, Alexander; Delhomme, Patricia; Gélinas, Isabelle (Frontiers in Neurology, 2019)
Introduction: Driving an automobile is an important activity for the social participation of individuals with traumatic brain injury (TBI). Return to safe driving is usually addressed during rehabilitation, but we know little about driving behaviors in the years following TBI rehabilitation. Objective: To explore self-reported and objective (official driving records) post-rehabilitation driving behaviors and offences in individuals with TBI: a) having passed a driving evaluation, b) who did not undergo a driving evaluation, and c) non-injured controls. Methods: Cross-sectional design with 162 adults: a) 48 participants with mild, moderate, or severe TBI whose drivers’ license was suspended and reinstated following a driving evaluation during rehabilitation (TBI-DE; M=42.2 years of age, SD=11.5); b) 24 participants with TBI who maintained their driving privileges without undergoing a driving evaluation (TBI-NE; M=36.5 years of age, SD=9.9); c) 90 non-injured controls (M=43.8 years of age, SD=11.4). Participants with TBI were recruited from seven rehabilitation centers, 2-3 years after the end of rehabilitation in the province of Quebec, Canada. During a telephone interview, data were obtained regarding self-reported driving: a) habits; b) self-efficacy; c) anger expression; d) sensation-seeking; e) violations/errors; f) accidents, driving offences, and demerit points for the two-year interval predating the study. Objective data for driving offences, accidents, and demerit points were obtained from the automobile regulatory body for the same period and for the two-year interval before the injury for the TBI groups. Results: Compared to non-injured controls, the TBI-DE group reported significantly lower scores for self-reported verbal aggressive expression of anger and driving violations/errors. Conversely, their official driving records showed significantly more demerit points for the last two years, and a significantly higher frequency of serious post-rehabilitation accidents (10), compared to the TBI-NE group (one) and the control group (none). Compared to pre-injury levels, individuals with TBI had significantly more demerit points post-rehabilitation. Conclusions: Individuals with TBI may underestimate risky driving behaviors even if they have been deemed fit to drive. Reduced self-awareness, memory, and dysexecutive problems following TBI could influence self-report of driving behaviors and explain discrepancies between self-reported and objective driving-related behaviors. Recommendations for research and practice are provided.